Sex‐Related Embryotoxicity of Pulp Mill Effluent Extracts in Medaka (Oryzias latipes) Female Leucophore‐free FLFII Strain. (29th June 2021) - Orrego, Rodrigo; Guchardi, John; Beyger, Lindsay; Barra, Ricardo; Hewitt, L. Mark; Holdway, Douglas
Abstract: The aim of the present study was to evaluate the effects of exposure to Chilean pulp mill effluent extracts on developing postfertilized medaka embryos before and after sex definition relative to sex steroids (testosterone and 17beta‐estradiol) and a wood phytoestrogen (beta‐sitosterol). Our study included 2 waterborne semichronic exposure experiments, using a 24‐h post fertilization (hpf) unknown‐sex FLFII (female leucophore free) group and a second 72‐hpf FLFII phenotypic sex‐identified group (male autofluorescence leucophore) strain of medaka embryos. Chronic exposure of both FLFII strain embryo groups showed similar delay in time to hatch and decreased hatchability. Teratogenic responses such as vertebral malformation (fusion, incomplete formation, and lack of vertebral formation process) and pericardial edema were observed in both experiments, with a high percentage related to FLFII fluorescent leucophore–identified males. In addition, high mortality associated with severe malformations was observed in male and female embryos exposed to testosterone. Our research has demonstrated that exposure to Chilean mill effluent extracts caused severe male medaka embryotoxicity (in postfertilized embryos) before and after sex definition and, irrespective of the experimental group and effluent treatment, suggests partial removal following secondary treatment. Furthermore, differences in the severity and type of teratogenic effects with previous experiments (d‐rR medaka strain), are associated with the unique phenotypes of this medaka mutant strain. Environ Toxicol Chem 2021;40:2297–2305. © 2021 SETAC